Promoting maternal mental health in Ghana: An examination of the involvement and professional development needs of nurses and midwives - Adjorlolo, S.; Aziato, L.; Akorli, V.V. (Nurse Education in Practice, 2019)
Insight into the involvement and professional development needs (PDNs) of non-mental health nurses and midwives with respect to promoting maternal mental health is necessary to integrate mental health services into primary healthcare delivery. Using a cross-sectional survey and self-report methodology, the study investigates the involvement, PDNs, knowledge and attitudes of 309 nurses and midwives in promoting maternal mental health in Ghana. Data were analyzed using descriptive and inferential statistics, namely Analysis of Variance, bivariate and logistic regression, and cluster analysis. The results showed that the majority of the participants (94%) indicated they were involved in promoting maternal mental health. Knowledge about maternal mental health correlated significantly with involvement in promoting maternal mental health (p < .05), whereas attitude towards maternal mental health did not. An overwhelming proportion of the participants (83%–94%) expressed profound interest in professional development education across a range of maternal mental health areas. Enhancing the mental health knowledge-base of nurses and midwives could contribute significantly to promoting maternal mental health.
Research Article
Keywords: Pregnancy; Mental illness; Maternal mental health; Nurses; Midwives; Ghana; Africa